Citotoxicity of different amounts of sodium hypochlorite on human cultured osteoblasts - Tatiana Kelly da Silva Fidalgo; Roberta Barcelos; Débora Barreiros Petrópolis; Bruno Rocha Azevedo; Laura Guimarães Primo; Fernando Costa e Ssilva Filho (Faculdade São Leopoldo Mandic, 2009)
Objective: To evaluate the cytotoxic effect of different amounts of sodium hypochlorite, on a culture of human osteoblastos (HOB) cells.Method: Cultures of human osteoblasts (HOB) in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% of bovine fetal serum were incubated in sodium hypochlorite (concentrations of 0.5; 1.0; 2.5 and 5.25%) for thirty seconds. The control group was represented by cells incubated in phosphate buffered saline (PBS). Cell viability was assessed by means of 0.4% trypan blue dye exclusion test, in triplicate. During the incubation period, images were recorded through an inverted optic microscope to evaluate the cellular morphology. Results: In the control group 98.7% of viable cells were verified, without morphology alterations, while no viable cells were observed in the experimental groups. The kinetics of cytotoxity was concentration-dependent. Conclusion: It was concluded that there was a cytotoxic effect on cultures of human osteoblasts incubated for thirty seconds in sodium hypochlorite in all concentrations (0.5; 1.0; 2.5 and 5.25%)